PENGARUH METODE MICROWAVE-ASSISTED EXTRACTION (MAE) DENGAN PELARUT NATURAL DEEP EUTECTIC SOLVENT (NADES) EKSTRAK DAUN MANGGA GEDONG TERHADAP KADAR TOTAL FLAVONOID DAN AKTIVITAS ANTIOKSIDAN - Latifah, Fadzil; Nuh, Muhammad (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Antioxidant activity with flavonoids has a strong relationship because it is influenced by the functional groups attached to the main structure. This study aims to determine the effect of solvents and extraction methods used on total flavonoid levels and antioxidant activity of gedong mango leaf extract. Gedong manggo was extracted using teh MAE-NADES combination method (sodium acetate and lactic acid solvents 1:3 in distilled water until temperature reached 70 ). Gedong mango were extracted in terms of temperature and time (80 :20', 80 :10', 60 :20', 60 :10'). Next, the value of total flavonoid content and antioxidant activity was determined for the extract. The results showed that gedong mango leaf extract had high total flavonoid content values, with respective values of 80 :20' 6.5994%, 80 :10' 5.5504%, 60 :20' 5.0890%, and 60 :10' 3.8902%. In addition, gedong mango leaf extract has antioxidant activity, with IC50 value of 80 :20 ' 21.666 ppm, 80 :10' 39.734 ppm , 60 :20' 61.687 ppm, and 60 :10' 135.487 ppm. From the results of the study it can be concluded that the MAE method using NADES solvent has values for total flavonoid levels and antioxidant activity. The best gedong mango leaf extract was at temperature and time of 80:20 '. Where the total value of flavonoids is directly proportional to the antioxidant activity, the higher the value of the flavonoid compounds produced, the higher the antioxidant activity.